An oncological curiosity of a male patient with a huge leiomyoma of the terminal ileum - Syaza Zainudin; Saravana Kumar Rajanthran; Nornazirah Azizan; Firdaus Hayati; Joriana Ginawoi; Khairunnisa Aini Suhaimi; Wan Yee Lilian Voo; Mohd Fazri Kiram; Muhammad Izzuddin Md Jaki; Siti Haja Abd Aziz; Subashini Thevi Nach Nacathiran (2020)
Leiomyoma is a smooth muscle tumour that can arise in any part of the body especially the uterus. Even though it is traditionally linked with hormonal inf luence, it can also develop in extrauterine organs with a slight female predominance. It is indistinguishable with gastrointestinal stromal tumour (GIST) histologically. We report a case of a 30-year-old gentleman who presented with a huge painful mass in the right iliac fossa. Computed tomography revealed a 10 × 10 cm homogeneous mass arising from the terminal ileum; he subsequently underwent an open right hemicolectomy. Histology showed a well-circumscribed lesion composed of interlacing bundles of smooth muscle fibres of the submucosa with positive smooth muscle actin and H-Caldesmon stains but negative for DOG-1 and CD117 (c-kit) stains which were consistent with leiomyoma. Despite its rarity, this hormone-related tumour needs to be considered regardless of gender. Immunohistochemistry is paramount as it is histologically identical to GIST.